2004
DOI: 10.1007/s00122-004-1843-1
|View full text |Cite
|
Sign up to set email alerts
|

An SSR- and AFLP-based genetic linkage map of tall fescue (Festuca arundinacea Schreb.)

Abstract: Tall fescue (Festuca arundinacea Schreb.) is commonly grown as forage and turf grass in the temperate regions of the world. Here, we report the first genetic map of tall fescue constructed with PCR-based markers. A combination of amplified fragment length polymorphisms (AFLPs) and expressed sequence tag-simple sequence repeats (EST-SSRs) of both tall fescue and those conserved in grass species was used for map construction. Genomic SSRs developed from Festuca x Lolium hybrids were also mapped. Two parental map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 45 publications
5
66
0
1
Order By: Relevance
“…Over half of the markers showed Mendelian segregation ratios, with the majority segregating 1:1. Saha et al (2005) reported similar findings for the markers segregating in their mapping population. Thirty nine percent of the markers showed segregation distortion which is higher than the 23% marker segregation disorder reported by Saha et al (2005) using similar markers for the construction of their genetic linkage map of tall fescue.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Over half of the markers showed Mendelian segregation ratios, with the majority segregating 1:1. Saha et al (2005) reported similar findings for the markers segregating in their mapping population. Thirty nine percent of the markers showed segregation distortion which is higher than the 23% marker segregation disorder reported by Saha et al (2005) using similar markers for the construction of their genetic linkage map of tall fescue.…”
Section: Discussionsupporting
confidence: 67%
“…Of these, 43 were polymorphic in parent ATM-21, 72 were polymorphic in parent 110-7, and the remaining 20 were segregating from both parental genotypes. As reported by Saha et al (2005), Mendelian inheritance of 1:1 and 3:1 is expected for the segregating molecular markers because tall fescue is an allohexaploid with disomic inheritance. Sixty-one percent of the markers scored followed normal…”
Section: Molecular Marker Analysismentioning
confidence: 72%
See 2 more Smart Citations
“…As EST-SSRs markers are derived from transcribed regions, they are likely to have a high success of amplification and associated gene annotations (Varshney et al 2005), and are useful for in silico comparisons to the homologous sequences in other species (Bushman et al 2008). EST-SSR markers have been used in genetic and comparative mapping in a number of forage grass species (e.g., Jones et al 2002b;Warnke et al 2004;Saha et al 2005;Alm et al 2003;Studer et al 2008). Additionally, EST libraries with long sequence reads constitute crucial reference sequences for further sequencing and functional genomics studies using ''Next-Generation'' methods.…”
Section: Introductionmentioning
confidence: 99%